A Study of Technological Gaps in Pineapple Cultivation in Darjeeling District of West Bengal - Roy, Deepa; Bandyopadhyay, AK (Indian Journal of Extension Education, 2021)
The study on pineapple production technology adoption was conducted in Phansidewa Block of DarjeelingÂ district of West Bengal state. The technological gap for marginal farmersâ€™ ranged from 97.11 to 32.00 per cent whereas, the marginal farmers had very little knowledge about the post-harvest technology, thus resulted poorÂ quality. Technological gap of small farmersâ€™ ranged from 27.77 to 94.00 per cent. The technological gap for medium farmers ranged from 14.00 to 86.11 per cent. Farmers in general were not fully aware of all the recommendedÂ scientific practices. It was also evident that the farmers in general were having maximum technological gap in fertilizer application. It has been advocated that a blank recommendation for all categories of farmers will notÂ serve the purpose hence location and farmer specific recommendations need to be devised.